2009
DOI: 10.1136/thx.2008.102228
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ventilator settings and acute lung injury after elective surgery: a nested case control study

Abstract: Background: While acute lung injury (ALI) is among the most serious postoperative pulmonary complications, its incidence, risk factors and outcome have not been prospectively studied. Objective: To determine the incidence and survival of ALI associated postoperative respiratory failure and its association with intraoperative ventilator settings, specifically tidal volume. Design: Prospective, nested, case control study. Setting: Single tertiary referral centre. Patients: 4420 consecutive patients without ALI u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
5
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 39 publications
3
119
5
6
Order By: Relevance
“…Blum et al (6) showed that the incidence of postoperative ARDS was 0.2% in a general surgical population and the intraoperative risk factor included driver pressure instead of low tide volume. In thoracic surgery, the expected incidence of postoperative ALI was as high as 4.2% (7) and the independent risk factors included intraoperative ventilatory pressure index instead of VT. Fernández-Pérez et al (8) designed a study to prove their hypothesis that higher VT would be associated with higher risk of respiratory failure secondary to ALI, but the result showed that mean first hour peak airway pressure but not VT was associated with ALI. The clinical researches above made us reconsider to utilize the ventilation mode with lower airway pressure during high risk operations especially thoracic surgeries with obligated OLV.…”
Section: Original Articlementioning
confidence: 99%
“…Blum et al (6) showed that the incidence of postoperative ARDS was 0.2% in a general surgical population and the intraoperative risk factor included driver pressure instead of low tide volume. In thoracic surgery, the expected incidence of postoperative ALI was as high as 4.2% (7) and the independent risk factors included intraoperative ventilatory pressure index instead of VT. Fernández-Pérez et al (8) designed a study to prove their hypothesis that higher VT would be associated with higher risk of respiratory failure secondary to ALI, but the result showed that mean first hour peak airway pressure but not VT was associated with ALI. The clinical researches above made us reconsider to utilize the ventilation mode with lower airway pressure during high risk operations especially thoracic surgeries with obligated OLV.…”
Section: Original Articlementioning
confidence: 99%
“…Bu olguların takiplerinde 2 yıllık mortalite %40 olarak bildirilmektedir (17). Preoperatif dönemde akciğer parenkimi ile ilgili ya da primer ya da sekonder restriktif nedenlere bağlı solunumsal sorunları bulunan hastalarda postoperatif solunumsal komplikasyonlar artar (18). Çalışmamızda KOAH'ı bulunan hastalarda preoperatif SpO 2 'nin düşüklüğü mevcuttu ve bu hastalarda preoperatif YB'a kabulün anlamlı olarak arttığı görüldü.…”
Section: Discussionunclassified
“…ARDS is a leading cause of postoperative hypoxemic respiratory failure with reported prevalence of 3 to 9% and associated mortality rates between 27 and 45% (19,20). As many as 20% of patients undergoing cardiac surgery will develop ARDS during the perioperative period, with a mortality as high as 80% (21).…”
Section: Discussionmentioning
confidence: 99%